Ideologi dan Perubahan Politik: Studi Terhadap Perubahan Politik pada Era Soeharto (1965- 1971) - Sinaga, Tatang Mulyana; Sitepu, Anthonius (Politeia: Jurnal Ilmu Politik, 2018)
For the change of view towards Communism that occurred in the era of Soekarnos government with the era of the Soeharto government, political changes took place. In the political era Soeharto (1965-1971) was a time vulnerable which could be categorized as a process of political transition from the Old Order to the New Order. This study uses a literature study with a qualitative approach aimed at describing Ideology and Political Change; Study of Political Change in the Suharto Era (1965-1971). The technique of collecting data uses literature, books, journals related to the political changes in the Soeharto era (1965-1971). The technique of data analysis uses a literature analysis approach. Soehartos political era can discourse that communism is very dangerous for the existence of Pancasila as the state ideology. Communism that is not godly is considered immoral, it is not suitable to be applied in Indonesia, which is religious and virtuous. In the era of Soehartos politics in general, political changes took place which were a stage of political reform. However, with the analysts emphasis on the essence of these political changes, the political changes that have taken place in the political era are more precisely said to be a stage of political decline (political regression).